Building resilience: quantity surveyors in the face of future pandemics - Matshete Modiba; Nishani Harinarain (Journal of Construction Project Management and Innovation)
This paper investigates the transformative impact of the global pandemic in the field of quantity surveying, specifically focusing on the challenges encountered by quantity surveyors and the resultant modifications in their professional activities. The study aims to equip quantity surveyors with valuable insights, fostering resilience to enable them to adapt and thrive amidst adversities. Employing a qualitative research approach, this study utilises interviews to delve into the challenges faced by quantity surveyors and identifies the essential traits necessary for future resilience. Six experienced quantity surveyors were purposively selected for in-depth interviews, and the collected data were subjected to thematic analysis to uncover prevailing trends and themes. The study reveals a spectrum of direct and indirect effects induced by the pandemic within the quantity surveying profession. Noteworthy impacts include alterations in work dynamics, modifications in site evaluations, increased instances of cost overruns, shifts in contract interpretation, and changes in the preparation of monthly payment certificates. As uncovered by the findings, resilience is not synonymous with avoiding challenges; instead, it involves the ability to adapt, learn, and grow stronger through adversity. Adopting resilient practices and mindset is crucial for quantity surveyors to navigate uncertainties and challenges effectively. This research not only enhances the resilience of quantity surveying as a profession but also imparts valuable lessons for mitigating the impact of future pandemics. By understanding the challenges and adaptations brought about by the pandemic, quantity surveyors can proactively shape their practices, ensuring a robust and resilient future for the profession.